IMMIGRATION DETERRENCE AGAINST INDONESIAN WHO AFFECTED BY RADICAL EXPERIENCES: ANALYSIS IN THE CONCEPT OF HUMAN RIGHTS - Agung Joko Prasetyo; Frissilya Angelina (Polteknik Imigrasi, 2019)
ISIS is a radical group in the name of Islam as a reference in acting, becomes a hot topic in the status quo due to the impact of its actions that can destroy and divide the Indonesian nation. The interance of ISIS is by the recruitment of closest people or family because in this way it is considered very effective in influencing. ISIS which enter Indonesia is mostly brought directly by Indonesian itself who previously lived/ worked abroad and has been indoctrinated with ISIS radical and with government regulations that forbid Indonesian citizens from being refused entry into their own countries making the spread of the Islamic State much more difficult to prevent and control their existence. It is stated in the Immigration Act which prohibits its citizens from being denied entry. It is a Government, especially the Directorate General of Immigration job, who has direct authority to regulate the crossing of every person entering and leaving Indonesian territory. Some challenges that are often found such as the use of